Fixed-Dose Combination Formulations in Solid Oral Drug <break/>Therapy: Advantages, Limitations, and Design Features - Christi A. Wilkins; Hannlie Hamman; Josias H. Hamman; Jan H. Steenekamp (MDPI AG, 2024)
Whilst monotherapy is traditionally the preferred treatment starting point for chronic conditions such as hypertension and diabetes, other diseases require the use of multiple drugs (polytherapy) from the onset of treatment (e.g., human immunodeficiency virus acquired immunodeficiency syndrome, tuberculosis, and malaria). Successful treatment of these chronic conditions is sometimes hampered by patient non-adherence to polytherapy. The options available for polytherapy are either the sequential addition of individual drug products to deliver an effective multi-drug regimen or the use of a single fixed-dose combination (FDC) therapy product. This article intends to critically review the use of FDC drug therapy and provide an insight into FDC products which are already commercially available. Shortcomings of FDC formulations are discussed from multiple perspectives and research gaps are identified. Moreover, an overview of fundamental formulation considerations is provided to aid formulation scientists in the design and development of new FDC products.